2021
DOI: 10.3389/fmolb.2021.732256
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Metabolites: The Emerging Hotspot of Antiviral Compounds as Potential Candidates to Avert Viral Pandemic Alike COVID-19

Abstract: The present global COVID-19 pandemic caused by the noble pleomorphic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has created a vulnerable situation in the global healthcare and economy. In this pandemic situation, researchers all around the world are trying their level best to find suitable therapeutics from various sources to combat against the SARS-CoV-2. To date, numerous bioactive compounds from different sources have been tested to control many viral diseases. However, microbial metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 309 publications
(231 reference statements)
0
14
0
Order By: Relevance
“…Flavonoids such as quercetin, hespertin and naringin show anti-viral activities [ 123 ], and apigenin, vitexin, and their derivatives have been shown to be effective against hepatitis C virus, herpes simplex virus 1(HSV-1), human hepatitis A, B, and C, rhesus rotavirus (RRV), and influenza viruses [ 124 ]. As a result of the rich metabolic potential of endophytes, there is an emerging interest in the development and use of microbial secondary metabolites as anti-viral agents [ 125 ]. To find anti-viral compounds with activities against SARS-CoV2, endophytic bacteria were isolated from various tissues of 16 medicinal plants at the University of Chittagong in Bangladesh.…”
Section: Production Of Secondary Metabolitesmentioning
confidence: 99%
“…Flavonoids such as quercetin, hespertin and naringin show anti-viral activities [ 123 ], and apigenin, vitexin, and their derivatives have been shown to be effective against hepatitis C virus, herpes simplex virus 1(HSV-1), human hepatitis A, B, and C, rhesus rotavirus (RRV), and influenza viruses [ 124 ]. As a result of the rich metabolic potential of endophytes, there is an emerging interest in the development and use of microbial secondary metabolites as anti-viral agents [ 125 ]. To find anti-viral compounds with activities against SARS-CoV2, endophytic bacteria were isolated from various tissues of 16 medicinal plants at the University of Chittagong in Bangladesh.…”
Section: Production Of Secondary Metabolitesmentioning
confidence: 99%
“…Various microbially derived metabolites serve as ligands to xenobiotic nuclear receptors. Microbial metabolites with host protective properties (e.g., intestinal inflammation/obesity and short-chain fatty acids, indole metabolites), per se, have been proposed as sources for developing new drugs (Giddings and Newman 2013, Saha, Rajpal et al 2016, Stringlis, Zhang et al 2018, Descamps, Herrmann et al 2019, Raihan, Rabbee et al 2021, Ramírez-Rendon, Passari et al 2022). The use of purified microbial metabolites as drugs has had mixed results.…”
Section: Endogenous Microbially-derived Ligands For Xrs and Their Use...mentioning
confidence: 99%
“…Based on cell culture assays, an anti-parasitic microbial product named ivermectin could inhibit the RdRp of SARS-CoV-2 with an IC 50 of 2.2–2.8 μM (Heidary and Gharebaghi 2020 ) and the clinical trials of ivermectin is in progress ( www.ClinicalTrials.gov -NCT04390022, NCT04602507). Recently Raihan et al (Raihan et al 2021 ) reported a comprehensive review on antiviral microbial metabolites, their classification and the viral targets. According to their report, fungi are responsible for 67% of microbial derived antivirals followed by bacteria (28%).…”
Section: Natural Based Therapeutics For Inhibition Of Sars-cov-2 Infe...mentioning
confidence: 99%